Wind load impact on tall building facades: damage observations during severe wind events and wind tunnel testing - Metwally, Omar; Ibrahim, Haitham A.; Elawady, Amal; Zisis, Ioannis; Chowdhury, Arindam Gan (Frontiers in Built Environment, 2025)
As global urbanization accelerates, the construction of tall buildings has surged, becoming a defining feature of modern cityscapes. Tall buildings, while contributing to economic growth and urban development, face substantial risks from extreme wind events, such as hurricanes and downbursts. This study provides a comprehensive evaluation of the performance of tall building facades under severe wind conditions, with a focus on recent events that impacted the Gulf Coast of the United States, specifically in Houston, during May to July 2024, including a powerful derecho and Hurricane Beryl. Through extensive damage assessments of various tall buildings, this research highlights the different damages observed from these wind events, revealing critical vulnerabilities in tall building façades, particularly in relation to wind channeling effects in densely built urban areas. The observed damage patterns, including extensive glass breakage and façade failures, underscore the need for a reassessment of wind effects on tall buildings to better reflect the complex interactions between wind forces and urban environments. Additionally, by integrating real-world damage observations with wind tunnel simulations carried out at the NSF NHERI Wall of Wind Experimental Facility, this research offers valuable insights into the factors that may have influenced the observed damage. In this wind tunnel testing campaign, a series of aerodynamic testing of a tall building model under both atmospheric boundary layer and downburst winds were conducted. Additionally, interference effects are tested for both types of events. The preliminary findings have shown that downburst winds can have higher negative pressures compared to atmospheric boundary layer (ABL) which needs to be further studied including several downburst events to characterize the difference between both types of winds. Also, the results indicated the need to conduct a detailed interference study to compare ABL and downburst to properly include these effects for dense urban areas.